Language Politeness Strategies Spoke by Boy William in the Breakout Interview with Ruel - Rifti Asri Meiliana; Rahmawati Sukmaningrum; Th. Cicik Shopia B. (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to (1) find out the types of politeness strategies spoken by Boy William in a breakout interview with Ruel, (2) find the most dominant politeness strategies, and (3) find the contribution of politeness strategies from a pragmatic perspective. This research is qualitative. The research data is in the form of a conversation between Boy William and Ruel in the talk show